Microbial Contamination of Buffalo Milk Dangke from Curio Enrekang of South Sulawesi - Hafsan, . (Proceeding Buffalo International Conference, 2013)
This study was conducted to determine the level of microbial contamination on buffalo milk dangke from Curio Enrekang of South Sulawesi. Samples assayed were taken directly from the manufacturers and seller of buffalo milk dangke shortly after the process of dangke making is finished. Microbial contamination was analyzed by a serial of microbiological test, i.e. Total Plate Count (PCT), MPN coliform, MPN Escherichia coli, Salmonella sp and Staphylococcus aureus. The results of those tests were then compared to the acceptable maximum limit of microbial contamination for dairy products according to SNI 01-6366-2000 in 2011. The results of the study showed that all dangke samples were contaminated by the bacteria to the extent of more than acceptable maximum level. Test results for Staphylococcus aureus indicated that contamination of these bacteria on dangke was still lower than the maximum level for human consumption.Â Additionally, there were negative results of both Escherichia coli and Salmonella sp on all dangke samples.